The Potential of Waste Cooking Oil B20 Biodiesel Fuel with Lemon Essential Oil Bioadditive: Physicochemical Properties, Molecular Bonding, and Fuel Consumption - Permanasari, A.A. (Diponegoro University, 2021)
This study is motivated by the depletion of fossil fuels in nature, which is inversely proportional to the higher level of fuel oil consumption, so the need for alternative fuels, namely biodiesel. Biodiesel can be made using waste cooking oil because of its abundant quantity, low price, and not being reused. One of the efforts to achieve energy conservation and improve fuel quality is using bioadditives. A lemon essential oil can be used as a bio-additive because it is easily soluble in fuel and its oxygen-rich content can reduce the rate of fuel consumption. The process in this study is to produce biodiesel with waste cooking oil (WCO) using a transesterification process. Biodiesel samples containing the bioadditive lemon essential oil on B20 biodiesel with varying volume fraction (0; 0.1; 0.15; 0.2). In general, this research can be done in three steps. The first step is the characterization of the compound composition (GCMS) and functional group (FTIR) of diesel fuel, biodiesel, and lemon essential oil bioadditive. The second step is the characterization of the physicochemical properties (density, viscosity, flash point, calorific value) of B20 biodiesel with various concentrations of lemon essential oil bioadditive, then compared with SNI 7182:2015. The third step is determining the rate of fuel consumption in diesel engines. The results show that Biodiesel B20 with a volume fraction of 2 lemon essential oil bioadditive has a high ability to reduce the rate of fuel consumption. Â© 2021 by Authors